Aluminium and zinc co-doped CuInS2 QDs for enhanced trion modulation in monolayer WS2 toward improved electrical properties. Issue 47 (20th November 2019) - Zhang, Jian; Wang, Bowen; Tebyetekerwa, Mike; Zhu, Yi; Liu, Boqing; Nguyen, Hieu T.; Tian, Shouqin; Zhang, Yupeng; Lu, Yuerui
Abstract : Precisely tuned trion ratios in monolayer WS2 with improved electrical properties are achieved by QD modification, exhibiting potential optoelectronic applications. Abstract : Considering the significant influence of trions on the optical and electronic properties of two-dimensional transition metal dichalcogenides, the precise tuning of trions in a large range is important for optoelectronic or trion-related applications. Herein, a detailed comparison of eco-friendly CuInS2 (CIS) quantum dots (QDs) and (Al, Zn) co-doped CIS QDs on tuning the trion ratio and electrical properties in a mechanically-exfoliated monolayer (ML) WS2 is presented. With a similar QD thickness, the trion modulation ability of CIS QDs is largely enhanced after co-doping due to existing extra donor states. In particular, the trion ratio of ML WS2 can be precisely tuned from 0.05 to 0.7 by varying the QD species and QD thickness, while only a small range (0.05–0.15) of the trion ratio in ML WS2 is achieved under gate voltage. Moreover, the electron mobility and electron concentration of WS2 -based field-effect transistors (FETs) are significantly improved after QD modification, exhibiting potential applications in FETs and photodetectors.